Corporate finance - Ross, Stephen A. (Irwin/McGraw-Hill, 1999)
Contents: Part 1 Overview: introduction to corporate finance; accounting statements and cash flow. Part 2 Value and capital budgeting : financial markets and net present value - first principles of finance; net present value; how to value bonds and stocks; some alternative investment rules; net present value and capital budgeting; strategy and analysis in using net present value. Part 3 Risk: capital market theory - an overview; return risk - the capital asset pricing model (CAPM); risk, return, and capital budgeting...